Influence of photodynamic therapy on the development of ligature-induced periodontitis in rats - Almeida, Juliano Milanezi de [UNESP]; Theodoro, Letícia Helena [UNESP]; Bosco, Álvaro Francisco [UNESP]; Hitomi Nagata, Maria Jose; Oshiiwa, Marie; Garcia, Valdir Gouveia [UNESP] (Amer Acad Periodontology, 2007)
Background: the purpose of this study was to evaluate, histologically and radiographically, the effect of photodynamic therapy on the progression of experimentally induced periodontal disease in rats.Methods: Ligatures were placed at the first mandibular molar in rats. The animals were divided into four groups: group 1 (C) received no treatment; group 2 was treated topically with methylene blue (MB; 100 mu g/ml); group 3 was treated with low-level laser therapy (LLLT); and group 4 was treated topically with methylene blue followed by LLLT (4.5 J/cm(2)) (photodynamic therapy; PDT). Rats were sacrificed 5, 15, or 30 days postoperatively. Standardized radiographs were taken to measure bone loss around the mesial root surface of the first molar. Data were analyzed statistically (analysis of variance and Tukey test; P < 0.05). A scoring system was used to evaluate the connective tissue, periodontal ligament, and alveolar bone histologically. Data were analyzed statistically (Kruskal-Wallis test; P < 0.05).Results: Radiographic examination showed that there was significantly less bone loss in Group PDT compared to Group C at 5 and 15 days postoperatively. There was no significant difference in bone loss at 30 days. At 15 days, the histologic results showed significant differences in the extent of inflammatory reaction in the gingival tissue, with a greater extent of chronic inflammatory reaction in Group LLLT.Conclusion: PDT transiently reduced the periodontal tissue destruction.
Keywords: alveolar bone loss; laser; photodynamic therapy